2022
DOI: 10.3390/ijms23042128
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Mechanisms of Snake Venom Induced Pain: It’s All about Location, Location, Location

Abstract: Pain—acute, chronic and debilitating—is the most feared neurotoxicity resulting from a survivable venomous snake bite. The purpose of this review is to present in a novel paradigm what we know about the molecular mechanisms responsible for pain after envenomation. Progressing from known pain modulating peptides and enzymes, to tissue level interactions with venom resulting in pain, to organ system level pain syndromes, to geographical level distribution of pain syndromes, the present work demonstrates that und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…The exact mechanism of nerve injury causing pain and CRPS in snakebite victims remains unclear. 10 Routine analgesics were insufficient for this patient's pain relief. Although antivenom administration can alleviate pain in areas distant from the bite site by neutralizing circulating and locally presented venom compounds, tissue edema and ischemia around the bite site may hinder the delivery of antivenom to the envenomation strike point, 3 leading to continued pain.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The exact mechanism of nerve injury causing pain and CRPS in snakebite victims remains unclear. 10 Routine analgesics were insufficient for this patient's pain relief. Although antivenom administration can alleviate pain in areas distant from the bite site by neutralizing circulating and locally presented venom compounds, tissue edema and ischemia around the bite site may hinder the delivery of antivenom to the envenomation strike point, 3 leading to continued pain.…”
Section: Discussionmentioning
confidence: 92%
“…Although antivenom administration can alleviate pain in areas distant from the bite site by neutralizing circulating and locally presented venom compounds, tissue edema and ischemia around the bite site may hinder the delivery of antivenom to the envenomation strike point, 3 leading to continued pain. 10 Therefore, it was decided to perform a regional nerve block with local anesthetics. As expected, this provided almost instantaneous pain relief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10], [11], [13] In the literature, components of snake venom such as PLA2, a serine protease, and metalloproteinase caused an indirect effect that if lots of venoms were injected during the bite, it causes pain in the abdomen, then it triggers nausea-vomiting. [18] From the result, it is found that 8 (14,5%) of the sample present with bleeding. The study by Masroori and Cesaretli found that only (8,5%) and (28,5%) of the sample were present with bleeding.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 94%
“…Acute localized moderate-to-severe pain is often documented as the first sign of a venomous snake bite (VSB). [ 2 , 3 ] The presynaptic and postsynaptic neurotoxins may directly interact with the nerve endings or indirectly cause severe pain secondary to ischemia due to local oedema. [ 1 ] Antivenom treatment fails to alleviate the local pain which may last for 48–72 h. [ 3 ] Weak opioids such as tramadol or paracetamol often provide inadequate analgesia.…”
mentioning
confidence: 99%